Global health 2050: the path to halving premature death by mid-century - Jamison, Dean T.; Summers, Lawrence H; Chang, Angela Y; Karlsson, Omar; Mao, Wenhui; Norheim, Ole F; Ogbuoji, Osondu; Schäferhoff, Marco; Watkins, David; Adeyi, Olusoji; Alleyne, George; Alwan, Ala; et al. (The lancet, 2024)
In Global Health 2050, the Lancet Commission on Investing in Health concludes that dramatic improvements in human welfare are achievable by mid-century with focused health investments. By 2050, countries that choose to do so could reduce by 50% the probability of premature death in their populations—ie, the probability of dying before age 70 years—from the levels in 2019. We call this goal 50 by 50. The interventions that enable achieving the goal of 50 by 50 should also reduce morbidity and disability at all ages. Historical experience and continued scientific advances suggest that 50 by 50 is a feasible aspiration. Seven of the 30 most populous countries have reduced their probability of premature death over the past decade at a rate that would halve the probability before 2050, including countries as diverse as Bangladesh, Ethiopia, Iran, and Türkiye. These focused gains can be achieved early on the pathway to full universal health coverage.
Gesehen am 06.10.2025